Acute Pulmonary Embolism Associated with Low-Dose Olanzapine in a Patient without Risk Factors for Venous Thromboembolism - Vu Hoang Vu; Nguyen Duong Khang; Mai Thanh Thao; Le Minh Khoi (Case Reports in Vascular Medicine)
Background. Olanzapine is a second-generation antipsychotic drug commonly prescribed for certain mental/mood conditions such as schizophrenia and bipolar disorders. This agent has been considered a precipitating factor for venous thromboembolism formation. Most of the cases previously reported were associated with high-dose olanzapine therapy or in patients with high-risk factors for the development of thromboembolism. Case Presentation. We report a patient who developed pulmonary embolism after a long course of low-dose olanzapine. A 66-year-old female patient suffering from insomnia had been prescribed olanzapine 2.5 mg and paroxetine 10 mg for two years. The patient suddenly developed a syncopal episode at home and was immediately brought to the hospital. The diagnosis of pulmonary embolism was made by chance during the computerized tomography of coronary arteries. The patient made a full recovery under conventional treatment and was discharged in stable condition. The thoracic computed tomography taken two months after discharge showed a completely normal pulmonary arterial tree. Conclusion. Olanzapine-associated pulmonary embolism is a rare entity and might be missed if the physician in charge is not vigilant and well informed. Even low-dose olanzapine can be associated with pulmonary embolism in patients with low classic risk factors if the treatment is prolonged. Pulmonary embolism should be sought in patients taking olanzapine even though the presenting manifestations are nonspecific.